A randomized double-blind noninferiority clinical multicenter trial on oral moxifloxacin versus placebo in the outpatient treatment of uncomplicated acute appendicitis: APPAC IV study protocol - Lund, Heidi; Haijanen, Jussi; Suominen, Saku; Hurme, Saija; Sippola, Suvi; Rantanen, Tuomo; Rautio, Tero; Mattila, Anne; Pinta, Tarja; Nordström, Pia; Kössi, Jyrki; Ilves, Imre; et al. (SAGE Publications, 2025)
BACKGROUND: Antibiotic therapy is currently considered a safe and effective treatment alternative for computed tomography (CT)-confirmed uncomplicated acute appendicitis with recent studies reporting good results on both oral antibiotics only and outpatient management. Furthermore, there are promising pilot results on uncomplicated acute appendicitis management with symptomatic treatment (placebo). This trial aims to assess whether both antibiotics and hospitalization can be safely omitted from the treatment of uncomplicated acute appendicitis.
METHODS: The APPAC IV (APPendicitis Acuta IV) trial is a randomized, double-blind, multicenter noninferiority clinical trial comparing oral moxifloxacin with oral placebo in an outpatient setting with a discharge directly from the emergency room (ER). Adult patients (18-60 years) with CT-confirmed uncomplicated acute appendicitis (absence of appendicolith, abscess, perforation, tumor, appendiceal diameter ⩾15 mm on CT, or body temperature >38 °C) will be enrolled in nine Finnish hospitals. Primary outcome is treatment success at 30 days, that is, the resolution of acute appendicitis resulting in discharge from the hospital without appendectomy during the 30-day follow-up evaluated using a noninferiority design with a noninferiority margin of 6 percentage points. Noninferiority will be evaluated using one-sided 95% confidence interval of proportion difference between groups. Secondary endpoints include postintervention complications, recurrent appendicitis after the 30-day follow-up, duration of hospital stay, admission to hospital and reason for admission, readmissions to emergency department or hospitalization, VAS pain scores, quality of life, sick leave, and treatment costs. The follow-up after discharge from the ER includes a phone call at day 1, and at 3-4 days, 30 days, and 1, 3, 5, 10, and 20 years. Those eligible patients, who decline to undergo randomization, will be invited to participate in a concurrent observational cohort study with follow-up at 30 days, and 1 and 5 years.
DISCUSSION: To our knowledge, APPAC IV trial is the first large randomized, double-blind, noninferiority multicenter clinical trial aiming to compare oral antibiotics and placebo for CT-diagnosed uncomplicated acute appendicitis in an outpatient setting. The study aims to bridge the major knowledge gap on whether antibiotics and hospitalization or both can be omitted in the treatment of uncomplicated acute appendicitis.
TRIAL REGISTRATION: The study protocol has been approved by the Clinical Trials Information System (CTIS) of the European Medicines Agency (EMA), study number: 2023-506213-21-00 and the trial has been registered in ClinicalTrials.gov, NCT06210269.